Arabic Language Learning Model Through Extracurricular Activities At Wali Songo Islamic Boarding School Ngabar Ponorogo - Nurul Abidin (Asalibuna, 2021)
The Wali Songo Islamic Boarding School located in the village of Ngabar Ponorogo which was established in 1961 is one of the cottages that implement Arabic language learning that combines formal and non-formal education. Non-formal education is carried out by teaching Arabic through extracurricular activities. The combination of these two learning models has proven to be able to produce alumni who are proficient in Arabic, both written and spoken.The type of research conducted by researchers in this study is qualitative. While the data acquisition is obtained in the field directly at the location of the data source. Data were also obtained from observations, interviews, and documentation.The purpose of this research is to find out what models have been implemented by Boarding School, how the implementation of the model, and how the results of the application of the model. So that this model is expected to be developed by the Boarding School and can inspire other institutions to improve the quality of Arabic learning for their students.The results of this study conclude that the Wali Songo Ngabar Islamic Boarding School in improving Arabic language skills, learning is not only delivered in class, but Arabic learning is applied and taught outside of class hours through extracurricular activities. There are several models of extracurricular activities in Arabic learning that are designed and have been practiced at the Wali Songo Islamic Boarding School Ngabar, namely: Ilqoul Mufrodat Jadidah (delivery of new vocabulary), Muhadatsah (conversation), Muhadhoroh (speech), Idhof lughowi (language tutoring), Shohafiyah (journalism), and Fanniyatul khoth (writing).